2004
DOI: 10.1200/jco.2004.07.060
|View full text |Cite|
|
Sign up to set email alerts
|

Selective CD4+ Lymphopenia in Melanoma Patients Treated With Temozolomide: A Toxicity With Therapeutic Implications

Abstract: TMZ at this dose and schedule results in CD4(+) lymphopenia in a majority of patients that can result in OIs. Pneumocystis pneumonia prophylaxis should be considered for patients who develop sustained lymphopenia on TMZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
163
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(172 citation statements)
references
References 14 publications
5
163
1
3
Order By: Relevance
“…This may be related to the temozolomide-free intervals in the dosage regime for melanoma. Temozolomide is known to affect T-cell counts, but mostly if administered continuously (33)(34)(35)(36). The considerable immune response rate may, moreover, reflect a beneficial effect of temozolomide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be related to the temozolomide-free intervals in the dosage regime for melanoma. Temozolomide is known to affect T-cell counts, but mostly if administered continuously (33)(34)(35)(36). The considerable immune response rate may, moreover, reflect a beneficial effect of temozolomide.…”
Section: Discussionmentioning
confidence: 99%
“…The considerable immune response rate may, moreover, reflect a beneficial effect of temozolomide. Several studies in mice have reported enhanced immunization after combining vaccination with temozolomide, or that temozolomide suppresses Treg function (4,(36)(37)(38)(39)(40). Chemotherapy may also suppress myeloid-derived suppressor cells (5).…”
Section: Discussionmentioning
confidence: 99%
“…TMZ is associated with CD41 specific lymphopenia, and the degree of iatrogenic immunosuppression caused by TMZ requires careful monitoring of these patients, who are at risk for the complications of immune deficiency. 18 Although it is used in some centers, we did not routinely offer prophylaxis for infections such as Pneumocystis carinii pneumonia, as very few cases have occurred in patients from our population base.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of several chemotherapeutic agents (eg, cyclophosphamide, temozolomide, or taxotere) have been shown to promote a desirable cytokine profile by inhibiting regulatory T-cells when administered at subtumoricidal levels. [34][35][36][37] Economic/Global Implications…”
Section: Immune Status In Acute Leukemiamentioning
confidence: 99%